Effect of dual therapy with liraglutide and ghrelin on brain metabolism and intracellular stress in the Huntington's disease R6/2 mouse model - Mena, Débora Tatiana de Sousa (2019)
Dissertação de Mestrado em Biologia Celular e Molecular apresentada à Faculdade de Ciências e Tecnologia